The Government’s Role in the Implementation of Religious Tolerance Practices in Southeast Asia - Mala, Fiki Khoirul; Supardin, Muhammad Ikhlas; Wahid, Muhammad Aminul (Millati: Journal of Islamic Studies and Humanities, 2022)
The dynamics of Islam within the framework of Islamic majority and minority groups cannot be separated from the government’s role in maintaining religious tolerance. Minority groups such as Moro Muslims in the Philippines, Patani Muslims in Thailand, and Rohingya Muslims in Myanmar have illustrated the government’s minimal role in resolving conflicts between the majority and minorities. Therefore, this paper discusses the Muslim majority and minority groups in several countries and their relationship with the government to implement the practice of religious tolerance. This article uses a library method with a content analysis approach from relevant articles related to the government’s role in implementing religious tolerance practices in Southeast Asia. The study shows that the existence of Islam as a belief of a person and the people who are part of the state and government cannot be separated from one another. In other words, the state’s support for its people of various ethnicity, cultures, and religions will contribute to the peace of the state and the creation of state stability. The position of the majority and minority in the religious process will also influence religious institutions socially, economically, and culturally. Showing the expression of diversity in religious practices in the Southeast Asia region will create a new order in creating peace.